Control of western corn rootworm via RNAi traits in maize: lethal and sublethal effects of Sec23 dsRNA. Issue 4 (2nd December 2019) - Vélez, Ana M; Fishilevich, Elane; Rangasamy, Murugesan; Khajuria, Chitvan; McCaskill, David G; Pereira, Adriano E; Gandra, Premchand; Frey, Meghan LF; Worden, Sarah E; Whitlock, Shannon L; Lo, Wendy; Schnelle, Karl D; et al.
Abstract: Background: RNA interference (RNAi) triggered by maize plants expressing RNA hairpins against specific western corn rootworm (WCR) transcripts have proven to be effective at controlling this pest. To provide robust crop protection, mRNA transcripts targeted by double‐stranded RNA must be sensitive to knockdown and encode essential proteins. Results: Using WCR adult feeding assays, we identified Sec23 as a highly lethal RNAi target. Sec23 encodes a coatomer protein, a component of the coat protein (COPII) complex that mediates ER‐Golgi transport. The lethality detected in WCR adults was also observed in early instar larvae, the life stage causing most of the crop damage, suggesting that WCR adults can serve as an alternative to larvae for dsRNA screening. Surprisingly, over 85% transcript inhibition resulted in less than 40% protein knockdown, suggesting that complete protein knockdown is not necessary for Sec23 RNAi‐mediated mortality. The efficacy of Sec23 dsRNA for rootworm control was confirmed in planta ; T0 maize events carrying rootworm Sec23 hairpin transgenes showed high levels of root protection in greenhouse assays. A reduction in larval survival and weight were observed in the offspring of WCR females exposed to Sec23 dsRNA LC25 in diet bioassays. Conclusion: We describe Sec23 as RNAi target for in planta rootworm control. High mortality in exposed adult and larvae and moderate sublethal effects in the offspring of females exposed to Sec23 dsRNA LC25, suggest the potential for field application of this RNAi trait and the need to factor in responses to sublethal exposure into insect resistance management programs. © 2019 Society of Chemical Industry Abstract : Sec23 is a new RNAi target for WCR, initially screened in adults, and confirmed in larval diet bioassays and transformed plants. Transcript knockdown, protein depletion and sublethal effects were evaluated.